Meningkatkan Hasil Belajar Siswa Dengan Penerapan Model Pembelajaran Problem Based Instruction Dan Make A Match Pada Materi Pokok Teorema Phytagoras - Nurdalilah Nurdalilah; Adek Nilasari Harahap; Yuni Rhamayanti (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The study aims to determine the increase in student learning outcomes. This type of research is class action research (PTK) using a learning model of Problem Based Instruction and Make a Match. In Cycle I show the average class earned at 63.8. The results of the final cycle II data analysis with the same learning is obtained by the average grade of 80.4. Based on the classical learning criteria, this learning has reached the target of learning. It can be concluded that through the learning model of Problem Based Instruction and Make a Match, there is an increase in student learning outcomes VIIII SMP Negeri 8 Padangsidimpuan increased. Keywords: Learning Outcomes, Learning Model Problem Based Instruction, Make a Match